A revision of the Myopsalta crucifera (Ashton) species group (Hemiptera: Cicadidae: Cicadettini) with 14 new species from mainland Australia - Popple, Lindsay W. (Zootaxa, 2017)
The genus Myopsalta Moulds is distributed throughout much of Australia. Previous studies have associated several undescribed species with the Myopsalta crucifera (Ashton) species complex. The present study informally divides the cicadas in the genus Myopsalta into two species groups. It provides a revision of the M. crucifera species group, which includes redescriptions of M. crucifera s. str. and M. mackinlayi (Distant). The identity of the latter species is further refined and attributed to material formerly presented under the name Myopsalta atrata (Goding & Froggatt). In addition to the redescriptions, 14 new species belonging to the M. crucifera species group are described, including M. albiventris n. sp., M. bassiana n. sp., M. chrysopedia n. sp., M. gordoni n. sp., M. leona n. sp., M. longicauda n. sp., M. majurae n. sp., M. melanobasis n. sp., M. parvula n. sp., M. platyptera n. sp., M. riverina n. sp., M. septa n. sp., M. umbra n. sp. and M. xerograsidia n. sp. A key to species in the genus Myopsalta is provided. Standard morphological descriptions and descriptions of calling songs unique to each species are included along with a discussion on different song types in the M. crucifera species group.